Authors (The Biblical archaeology review, 2020)
Ronald S. Hendel ("How Old Is the Hebrew Bible?") is the Norma and Sam Dabby Professor of Hebrew Bible and Jewish Studies at the University of California, Berkeley. His research focuses on textual criticism, the Hebrew Bible, and ancient Near Eastern religion.